Synergistic nanomedicine by combined gene and photothermal therapy - Kim, Jinhwan; Kim, Jihoon; Jeong, Cherlhyun; Kim, Won Jong (ELSEVIER SCIENCE BV, 2016)
To date, various nanomaterials with the ability for gene delivery or photothermal effect have been developed in the field of biomedicine. The therapeutic potential of these nanomaterials has raised considerable interests in their use in potential next-generation strategies for effective anticancer therapy. In particular, the advancement of novel nanomedicines utilizing both therapeutic strategies of gene delivery and photothermal effect has generated much optimism regarding the imminent development of effective and successful cancer treatments. In this review, we discuss current research progress with regard to combined gene and photothermal therapy. This review focuses on synergistic therapeutic systems combining gene regulation and photothermal ablation as well as logically designed nano-carriers aimed at enhancing the delivery efficiency of therapeutic genes using the photothermal effect. The examples detailed in this review provide insight to further our understanding of combinatorial gene and photothermal therapy, thus paving the way for the design of promising nanomedicines. (C) 2015 Published by Elsevier B.V.
Keywords: NEAR-INFRARED LIGHT; STIMULI-RESPONSIVE POLYMERS; KAPPA-B P65; DRUG-DELIVERY; TEMPERATURE-DEPENDENCE; GOLD NANOPARTICLES; CANCER-THERAPY; INTRACELLULAR TRAFFICKING; SIRNA DELIVERY; GRAPHENE OXIDE